Natural Hazards Risk Assessment and Vulnerability Reduction - Simão Antunes do Carmo, José (IntechOpen, 2018)
This book addresses different aspects of natural hazards and vulnerabilities, with a focus on prevention and protection. It consists of nine chapters, five on flood events addressing vulnerabilities, risk assessments, impacts, sensitivity analyses, and mitigation measures, two on climate change and reconstruction of natural hazard events such as avalanches and rockslides, and two on tsunamis and volcanoes. All chapters provide relevant information and useful elements for readers interested and concerned about the lack of action or its ineffectiveness in containing the vulnerabilities and risks of possible natural hazards worldwide.